Analisis Bibliometrik: Penerapan Pedagogi Genre pada Pembelajaran Bahasa - Sofiar, Elly; Safi’i, IImam; Hikmat, Ade (Universitas Mathla'ul Anwar Banten, 2024)
Genre Pedagogy is a text-based learning model. The learning process in the curriculum in Indonesia is to present language learning activities that refer to the Genre Pedagogy model. Articles that have been published contain many genre pedagogical models used in foreign language and non-language learning. Why was this research carried out? Looking at the digital-based conditions and times related to strong literacy skills in understanding various types of text. The aim of the research is to review literature related to the application of genre pedagogical learning models that use technology or are digitally based. The research method used is analysis or bibliometric methods sourced from Scopus and Crossref metadata using the Publish or Perish application. Based on searches and analysis using the Publish or Perish search system, it can be seen that there has not been a single study that specifically links it to digital-based Indonesian language learning. Thus, research is still needed on the application of digital-based genre pedagogy to Indonesian language learning.